Alfabetização de jovens e adultos no Estado da Paraíba: registros político-pedagógica de experiências da década de 1960. - Façanha, Sabrina Carla Mateus (2013)
This dissertation was intended to understand and record the pedagogical practices of the Campaign of Popular Education (CEPLAR), which emerged in 1961 in Paraíba and was extinguished with the military coup in 1964. The research belongs to the field of the Popular Education history and has as its main source of reference theoretical researchers such as Favero (1983), Beisegel (2008), Paiva (1973) and Scocuglia (2001). Thus, a rescue of the history of practices teaching adult literacy at national, regional and state level was performed placing the socio-economic and political context in the period of years 1960 - 64. The Military Police Inquiry (IPM) of Paraiba and its collections and newspaper clippings of the period were used as a primary source. We conducted an analysis of the methodologies and teaching materials of CEPLAR and ABC Crusade, the latter being an experiment in political and pedagogical opposition to Paulo Freire‟s System Literacy, used by CEPLAR. The results confirm the importance of education in the field of Youth and Adult Literacy history in order to understand the relationship of the diverse temporality and to promote the search for prospects of actions against the exclusion statistics that historically generated the problem of illiteracy in our country.